1982
DOI: 10.1073/pnas.79.20.6151
|View full text |Cite
|
Sign up to set email alerts
|

A bent monomeric conformation of myosin from smooth muscle.

Abstract: Smooth muscle myosin filaments formed in 0.15 M KCI are depolymerized by MgATP to a lOS component, rather than to the 6S component typical of myosin monomer in high salt concentrations. This lOS species is also monomeric as determined by sedimentation equilibrium and calculated from the diffusion and sedimentation coefficients. The conformation of lOS myosin is, however, very different from that of 6S myosin, which has a flexible but extended rod. The Stokes radius and the viscosity of lOS myosin are less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
196
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(216 citation statements)
references
References 34 publications
(27 reference statements)
20
196
0
Order By: Relevance
“…It is known, for example, that regulation is highly ionic strength-dependent (8), and it is increasing ionic strength to which HMM is subjected during rotary shadowing specimen preparation. These effects can be somewhat offset by using peptide crosslinkers, and in those few instances where a crosslinker has been used, a clearly more compact arrangement of the myosin heads can be detected, as predicted by our model (25,27).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…It is known, for example, that regulation is highly ionic strength-dependent (8), and it is increasing ionic strength to which HMM is subjected during rotary shadowing specimen preparation. These effects can be somewhat offset by using peptide crosslinkers, and in those few instances where a crosslinker has been used, a clearly more compact arrangement of the myosin heads can be detected, as predicted by our model (25,27).…”
Section: Discussionsupporting
confidence: 57%
“…Before this study, the only evidence for the structure of dephosphorylated smooth muscle HMM came from rotary shadowing electron microscopy of isolated molecules (25). Typically, these preparations reveal a conformation with the heads folded backwards toward the S2 domain (26).…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting to see whether vertebrate smooth muscle and nonmuscle myosins, which adopt the 10S monomer conformation requiring sharp bends at two constant positions within the rod (11,43), have similar proline-containing hinges. For striated muscle myosins, a hinge region has been postulated to exist about one-third of the way down the length of the rod, based on sequence analysis, electron microscopy, protease sensitivity, and biophysical measurements (for review see reference 19).…”
Section: The Hinge and Its Possible Role In Enzymatic Regulationmentioning
confidence: 99%
“…It has been reported that unphosphorylated gizzard myosin disassembly by ATP has a sedimentation coefficient of 10 S and a molecular mass of 500 kDa, the latter value being the same to that of 6-S myosin in 0.6 M KC1 [2,10]. The structural difference between the 6-S and 10-S forms of smooth muscle myosin has been clarified by electron microscopic studies as follows : while 6-S myosin in high-salt medium exhibits an extended tail, 10-S myosin in low-salt solution containing ATP shows a looped tail conformation with a crossing point between the S2 region of the myosin neck and the specific hinge at one-third from the C-terminus of the rod [2,11]. Accordingly, it is likely that ATP induces some structural changes in each filament component, that is, each myosin molecule.…”
mentioning
confidence: 86%
“…Formations of actin thin filament and myosin thick filament in smooth muscle and non-muscle tissues seem to be prerequisites for actomyosin to generate mechanical force for the contraction. Recently, evidence has been accumulating that Ca2 + calmodulin-dependent myosin light chain kinase phosphorylates the regulatory light chain, resulting in the assembly of myosins from various sources, including gizzard [I], aorta [2], thymus [3, 41, platelet [3] and thyroid [5]. However, the detailed mechanism of myosin assembly by the phosphorylation of its light chain remains to be investigated.…”
mentioning
confidence: 99%